Peranan Hukum Pajak Dalam Pembangunan Ekonomi Nasional Guna Mencapai Tujuan Negara - Anggi Kania Putri; Taun Taun (Peneliti.net, 2023)
This paper discusses the issue of the role of tax law in national economic development in order to achieve state goals in relation to tax law by using a functional approach to tax law. Therefore, the nature of tax law must be clarified in advance so that the concept of tax law in economic development in order to achieve state goals can be interpreted appropriately. This paper explains that taxes are used for state financial resources which are vital for the running of the country, besides that it is also a manifestation of state financing facilities in realizing the implementation of national development, because all government expenditures, including development expenditures, are funded by taxes, taxes are very important for the functioning of the state, especially in terms of implementing development.